Validity and Reliability Test of Assessment Instrument of the Suitability of Electric Power Steering Media - Nur Fitriyanto, Joko; Widjanarko, Dwi; Khumaedi, Muhammad Khumaedi (Universitas Negeri Semarang, 2019)
Assessment instrument is one of the important parts of a research, it should be suitable with the things that are going to work with. This research is purposed to test the validity and reliability of the instrument that is going to use to examine the visual aid media electric power steering. The validity analysis model used in this test is Content Validity Ratio or CVR to asses the validity of the instrument. Meanwhile, the reliability instrument is tested trough Intraclass Correlation Coefficient; ICC). The result showed that the points of the instrument reach the CVR number of 0.99 which means that the instrument is valid. Furthermore, the number of ICC is 0.835 (media expert instrument), 0,815 (material expert instrument) and 0,732 (user response instrument). From the findings, it can be concluded that the instruments for media and material experts are in high stability category, while the user response instrument can be categorized as adequate. Finally, these instruments are valid to asses the suitability of the electric power steering media.